2007
DOI: 10.1073/pnas.0701934104
|View full text |Cite
|
Sign up to set email alerts
|

Identity of a pathway for saccadic suppression

Abstract: Neurons in the superficial gray layer (SGS) of the superior colliculus receive visual input and excite intermediate layer (SGI) neurons that play a critical role in initiating rapid orienting movements of the eyes, called saccades. In the present study, two types of experiments demonstrate that a population of SGI neurons gives rise to a reciprocal pathway that inhibits neurons in SGS. First, in GAD67-GFP knockin mice, GABAergic SGI neurons that expressed GFP fluorescence were injected with the tracer biocytin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
69
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(74 citation statements)
references
References 23 publications
(39 reference statements)
3
69
2
Order By: Relevance
“…Previous studies have shown that there exist a variety of GABAergic neurons in the SGI, including interlaminar, intralaminar, commissural, and tectofugal projection neurons (Sooksawate et al, 2005;Lee et al, 2007). These various GABAergic neuronal types may have different functional roles in the SC circuitry.…”
Section: Anatomical Properties Of Gabaergic Neuronsmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies have shown that there exist a variety of GABAergic neurons in the SGI, including interlaminar, intralaminar, commissural, and tectofugal projection neurons (Sooksawate et al, 2005;Lee et al, 2007). These various GABAergic neuronal types may have different functional roles in the SC circuitry.…”
Section: Anatomical Properties Of Gabaergic Neuronsmentioning
confidence: 99%
“…These various GABAergic neuronal types may have different functional roles in the SC circuitry. For example, a population of interlaminar GABAergic neurons that project to the SGS may inhibit SGS neuronal activity, suppressing unwanted inputs during the course of a saccade (Lee et al, 2007).…”
Section: Anatomical Properties Of Gabaergic Neuronsmentioning
confidence: 99%
See 2 more Smart Citations
“…The LHAjd, via its bidirectional connections with the SC intermediate and deep layers, has the potential to modulate one or more of these processes; understanding how it may do this will likely require a better understanding of the topographic organization of the multilayered SC. In that regard, one recent study has shed some light on the intrinsic circuitry of the SC (Lee et al, 2007); specifically, it is proposed that the SCig enables saccadic suppression based on the finding of an inhibitory (GABAergic) projection from the SCig to the superficial (retino-recipient) SC layer in rats and mice (Lee et al, 2007). More recently, a PHA-L study of the medial and lateral parts of the SCig identified differences in their projections.…”
Section: Cerebrospinal Trunk: Motor Systemmentioning
confidence: 99%